[Rezension von: Anthony, Barry, Murder, mayhem and music hall] - Crone, Rosalind (Crime, histoire & sociétés, 2021)
"Rather than walk along the Strand," Barry Anthony tells us, at the end of the 19th century "the comedian Dan Leno found it cheaper to take a cab from one end to the other", as on foot his progress was impeded by the desperate and the criminal, beggars and swindlers, on the look out for mugs who would give them some cash (p. 129). Today, you are far more likely to suffer from the intolerable traffic fumes belched out by the many cars and buses which make use of one of London’s most important ...